PERUBAHAN SIFAT KIMIA TANAH DAN HASIL JAGUNG PADA INSEPTISOL DENGAN PEMBERIAN KOMPOS - Halasan Halasan; Anandyawati Anandyawati; Hasanudin Hasanudin; Riwandi Riwandi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2018)
[CHANGE IN SOIL CHEMICAL CHARACTERISTICS AND YIELD OF MAIZE IN AN INCEPTISOL AS AMENDED WITH COMPOST]. Vast area of inceptisol in Indonesia is a potential natural resource for improving the domestic maize production. The amendment of organic material is expected to make correction on the fertility problem inherent in the soil. Objective of this study was to determine the optimum dose of compost for some soil chemical properties and maize performances. The doses of compost consisted of 0, 2.5, 5, 7.5, 10, and 12.5 ton/haa were allotted randomly on the experimental plots according to completely randomized design with three replications. Observations were made on  the exchangeable Aluminum (Al-dd), pH, organic carbon, water content, plant height, unhusked and husked ear weight, and grain yield. Analysis of variance showed that the dose of compost had significant (P?0.05) effects on pH and C-organic in soil. Giving compost at a dose about 12.5 ton/ha could increase the pH about 4.9, whereas giving compost at a dose about 10 tonha-1 could increase C-organic about 3.09 %. In other hand, the giving of compost with various dose did not give significantly (P>0.05) affect towards  Aluminium (Al-dd), pH, C-organic, water content, height of plants, weight of without husk, weight of cob with husk, weight of dry corn beans. The highest grain yield (2,415.75 kg/ha) was observed on compost applied at  dose  12.5 ton/ha.